The Influence Of Tiktok Applications On The Consumption Behavior Of Adolescents In Online Shopping - Nurfan Erizal (Pena Cendekia Insani, 2021)
In this day and age, social media has become one of the most widely used things by people, especially teenagers, social media is online media that contains social interaction. Social media uses web-based technology that turns communication into interactive. Some of the most popular social media sites today include: Blogs, Twitter, Facebook, Instagram and the current trend is Tiktok. In the current pandemic, there are a lot of users of the tiktok application, ranging from those who only watch to become tiktok creators. Tiktok social media is an audio-visual media. This media is in the form of videos and photos made by juxtaposing various music. This media is a medium that disseminates the creativity and uniqueness of each user. Tik tok social media is a social media that provides unique and interesting special effects that can be used by its users. This social media can make users feel happy, because the videos they make with various music. By using this media, each user cannot only do it once or twice because they are so happy to use Tik Tok social media. Tiktok can also influence its users to shop online consumptively and unconsciously.